THERAPY OF II TYPE DIABETES MELLITUS: EFFICIENCY IS PROVED BY TIME - Муравльова, О.В. (World of Medicine and Biology, 2015)
This article covered the most actual problem of endocrinology diabetes mellitus (DM), that spreading with catastrophic speed, becoming a real epidemic of the XXI century. Metformin – is hypoglycemic preparation that proved its efficiency in II type diabetes mellitus treatment during several years. That is why Metformin is stable choice in the first-line hypoglycemic therapy.